Long term outcomes in patients with chronic right ventricular pacing upgraded to cardiac resynchronization therapy. (9th July 2019) - Rickard, John; Gorodeski, Eiran Z.; Patel, Divyang; Hussein, Ayman; Moennich, Laurie Anne; Cantillon, Daniel; Trulock, Kevin; Toro, Saleem; Niebauer, Mark; Varma, Niraj; Wilkoff, Bruce L.
Abstract: Introduction: In patients with chronic systolic heart failure and frequent right ventricular pacing (RVP), upgrade to cardiac resynchronization therapy (CRT) has become common practice despite a lack of randomized clinical trials. We aimed to evaluate long term outcomes in patients upgraded to CRT from chronic RVP compared with de novo CRT implants. Methods and results: We reviewed medical charts on consecutive patients with a left ventricular ejection fraction (LVEF) ≤ 35% and a QRSd ≥ 120 ms undergoing CRT. Survival free of left ventricular assist device (LVAD) and a heart transplant was compared amongst patients on the basis of pre‐CRT QRS morphology. Improvement in LVEF was also compared across groups. A total of 1260 patients met inclusion criteria of whom 233 were upgraded from chronic RVP. Over a mean follow up 6.5 ± 4.0 years there were 821 endpoints (27 LVAD, 30 heart transplants, and 764 deaths). In a multivariate Cox regression model, upgraded patients had worse outcomes (HR 1.3(1.1‐1.7) P = .007) compared with those with native LBBB and similar outcomes to patients with non‐LBBB(HR 0.96(0.76‐1.21) P = .7). The survival curve for chronic RVP parallels native LBBB for approximately 2.5 years before dropping sharply. Patients with chronic RVP derive similar improvements in LVEF compared with those with LBBB and superior improvements compared with those with non‐LBBB. Conclusions: Despite achieving similar levels of LVEF improvement, patients with systolic heart failure with chronic RVP undergoing upgrade to CRT have inferior long term outcomes compared with patients with native LBBB. Long term outcomes with CRT in patients with chronic RVP, RBBB, and IVCD are similar.